(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article outlines several advantages of laparoscopic surgery. It demonstrates that laparoscopic instruments provide surgeons with broad visibility and the ability to manually control working instruments through small incisions, which are designed to safely work in confined spaces while maintaining visual guidance and control.